Telenursing Benefits in patients with Diabetes: A Review Article - Imani, Asad; Dabirian, Azam (Advances in Nursing & Midwifery, 2014)
Telenursing Benefits in patients with Diabetes: A Review Article Imani A1, Dabirian A2 1. RN Alumnus MS Nursing Education. Department of Nursing and Midwifery. Shahid Beheshti University of Medical Sciences. Tehran. Iran2. MSN Faculty Member. Department of Medical –Surgical Nursing Faculty of Nursing and Midwifery. Shahid Beheshti University of Medical Sciences. Tehran. Iran. Corresponding author: Asad Imani; a_eimany67@yahoo. com Abstract Background and aim: Telenursing is an affordable، easy and available nursing intervention and nurses can use this method to overcome the obstacles related to time and place. The purpose of this review was to provide evidence for the impact of telenursing on diabetic patients outcomes. Method: An electronic search was performed for articles which were published in English and Persian languages on PubMed,BMJ,Conult Nursing,Magiran,SID, and IranDoc databases. The search was conducted using the following keywords: telephone-telephone follow up – telenursing – diabetic patients and quality of life of diabetics. These databases were searched in a time period of 2000 to 2012. Findings: 30 articles were included for review. Evidence indicated the positive effects of telenursing on some patient outcomes as control of blood glucose، adherence to diet and physical activity and improved quality of life in patient with diabetes. Conclusion: With regard to benefits of telenursing, it is recommended to include this affordable technology in health care programs. Key words: Diabetes، Telenursing ,Telephone follow-up، Blood glucose control، Quality of life